2010
DOI: 10.1021/jp104402u
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Double Layer Properties in Diameter Asymmetric Molten Salt Investigated by Grand Canonical Monte Carlo Method

Abstract: Results of the Monte Carlo simulation of the electrode | molten salt interface are reported. The system investigated is represented by a primitive model of electrolyte in contact with a planar charged hard wall. The density of an electrolyte is comparable with the density of real molten salts. The calculations are performed for T = 1500 K, which is above the phase transition temperature determined from Monte Carlo analysis of the heat capacity C V and the radial distribution function. The density and charge pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The edl structure consisting of alternatingly charged layers was assumed in numerous simulations [55][56][57][58][59][60][61][62], which indirectly confirm an importance of an interesting feature of EMImBF 4 [25] and BMPyBF 4 ionic-pairs [24]. Namely the BF À 4 anion does not form H-bonds with hydrogen atoms of the pyridinium ring, but it does in EMImBF 4 ionic complex.…”
mentioning
confidence: 62%
“…The edl structure consisting of alternatingly charged layers was assumed in numerous simulations [55][56][57][58][59][60][61][62], which indirectly confirm an importance of an interesting feature of EMImBF 4 [25] and BMPyBF 4 ionic-pairs [24]. Namely the BF À 4 anion does not form H-bonds with hydrogen atoms of the pyridinium ring, but it does in EMImBF 4 ionic complex.…”
mentioning
confidence: 62%
“…In Sec. III A, results from the DFT are compared with the Monte Carlo simulations of Lamperski and Kłos,13,14 and show good agreement with the simulations. Next, in Sec.…”
Section: Introductionmentioning
confidence: 71%
“…Further MC simulations of an asymmetric model in which the ions have different sizes showed a distorted bell-shape, with the maximum slightly negative of the pzc. 14 Recently, there have been a few atomistic molecular dynamics simulations of molten salts that studied the effects of electrode potential on the double layer. Reed et al 15 16 For atomically flat electrodes, they found a pronounced layering of the ions in the electrolyte near the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…measurements have begun to expose the limitations of the PM double layer. For example, ionic liquid double layers manifest a variety of C D versus electrode surface charge density σ behaviour [8][9][10][11], which can only be understood at best in rather broad terms using the RPM or the PM [12][13][14][15][16][17][18][19][20][21][22][23]. The primitive models necessarily introduce a shape symmetry in the constituent species of an electrolyte, which is probably not very realistic in the natural world.…”
Section: Introductionmentioning
confidence: 99%